Efficacy of pulmonary rehabilitation using cervical range of motion exercise in stroke patients with tracheostomy tubes - Cho, Sung-Hyoun (J Phys Ther Sci, 2015)
[Purpose] In this study, stroke patients who were intubated with tracheostomy tubes performed cervical range of motion exercises, and changes in their pulmonary and coughing functions were examined. [Subjects and Methods] Twelve stroke patients who were intubated with tracheostomy tubes participated in the study. The subjects were randomly assigned to either the control group (n=6), which did not perform cervical range of motion exercises, or the experimental group (n=6), which did perform exercises. [Results] With regards to forced vital capacity, forced expiratory volume at one second, and peak cough flow rate before and after the exercises, the control group did not show any significant differences while the experimental group showed statistically significant increases in all three parameters. [Conclusion] The results indicate that cervical range of motion exercises can effectively improve the pulmonary function and coughing ability of stroke patients intubated with tracheostomy tubes, and that cervical range of motion exercises can help in the removal of tracheostomy tubes.